« Il n'y aura point de nuit dans l'ordre combiné » : Charles Fourier du jour au lendemain. Issue 1 (1st April 2021) - BOUCHET, THOMAS
Abstract : The nights of Harmony will be bright, writes Charles Fourier: instead of the "pallid mummy" (the moon), dazzling stars will give them "the appearance of our gardens illuminated at parties with multi-coloured glasses". Each sleep will be but the prelude to a desired awakening. Fourier's thought, particularly in its cosmogonic dimension, is thus a call for us to overcome "civilized" nights, which are the realm of subjugation, boredom and suffering. Doing away with nights is a way of achieving the "absolute gap" dear to Fourier.